2020
DOI: 10.1097/iae.0000000000002607
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap Techniques and Outer Retinal Layer Structures

Abstract: Purpose: To examine the influence of the inverted flap (IF) internal limiting membrane (ILM) technique in macular hole (MH) closure on outer retinal layers after MH surgery. Methods: Retrospective study. Postoperative position of ILM, recovery rate of external limiting membrane and ellipsoid zone, and best-corrected visual acuity were evaluated. The Inserted group, where the IF is placed inside the hole, was compared with the Cover group, where the IF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…We always used the “cover” approach, but in Iwasaki’s series, more than half of the ILM flap eyes were treated with the “filling” approach where the inverted flap is placed inside the hole. That may mechanically interfere with the recovery of ELM, as has been recently reported [11, 14]. This might also explain why we couldn’t find any difference in the ELM recovery period (similar in the 2 groups 3 months after surgery), whereas Iwasaki et al [8]reported an ELM recovery period of 11 months in ILM flap eyes versus 3.4 months in ILM peeling eyes.…”
Section: Discussionmentioning
confidence: 53%
“…We always used the “cover” approach, but in Iwasaki’s series, more than half of the ILM flap eyes were treated with the “filling” approach where the inverted flap is placed inside the hole. That may mechanically interfere with the recovery of ELM, as has been recently reported [11, 14]. This might also explain why we couldn’t find any difference in the ELM recovery period (similar in the 2 groups 3 months after surgery), whereas Iwasaki et al [8]reported an ELM recovery period of 11 months in ILM flap eyes versus 3.4 months in ILM peeling eyes.…”
Section: Discussionmentioning
confidence: 53%
“…In the literature, various studies suggested that a single-layered flap provides superior morphological and functional results compared with multilayered flap or insertion technique. 12,25 So postoperative clear visualization of the ILM flap might provide us the chance of optimizing our surgical maneuvers to perform an ideal unfolded, unwrinkled single layered ILM flap aiming to gain the highest possible level of vision. In regard of this issue, our study suggests that en face OCT provides high quality images of the ILM flap to assess the location, configuration, and regularity of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, histopathological and immunohistochemical evaluation of ILM specimens peeled during vitrectomy show Müller cell footplates, vascular remnants neural tissue. 1927 Several studies in the literature stated that presence of the IRDs is not related with deterioration in BCVA, visual field analysis or mean retinal sensitivity. 8,15,16,27 Similarly, in our study the final BCVA was found to be related with neither the width, diameter and number of inner retinal dimples nor the configuration of the ILM flap.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated the dependence of functional improvement on the postoperative integrity of the outer retinal layers. Especially, the restoration of the external limiting membrane (ELM), ellipsoid zone (EZ), and outer photoreceptor segments (OS) were reported to significantly correlate with an improved postoperative best-corrected visual acuity (BCVA) [29][30][31][32][33][34][35]. Over the last 10 years, several modifications of the original I-ILM flap technique with similar favorable results have been described [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%